Upaya yang Dilakukan Diabetisi yang Menggunakan BPJS dalam Mengendalikan Gula Darah. - Maria Paulina Irma Susanti (Viva Medika, 2019)
Diabetes Mellitus is a chronic metabolic disease in which people with diabetes can not produce enough insulin or the body is unable to use insulin effectively resulting in excess sugar in the blood. Good blood sugar control is a key factor in preventing complications. This can be achieved by administering antidiabetic drugs, lifestyle changes, as well as regular blood glucose and laboratory measurements. Although research on the experience of people with diabetes in controlling blood sugar has been overwhelming, there remains a need to differentiate between factors and processes involved in other blood sugar controls such as the process in the use of BPJS for people with diabetes and gain experience of people with Type II diabetes who use BPJS in controlling blood sugar . This research is a qualitative research with 4 participants of BPJS users. The interviews were structured thematicly analyzed using a phenomenological approach. The result of the research is the exploration of the utilization of people with diabetes in controlling blood sugar, obstacles felt by people with BPJS in controlling Blood sugar, the attempts made by people with BPJS in controlling blood sugar. So it can be concluded that the theme obtained from the results of in-depth interviews can answer research questions that experience diabetisi using BPJS in controlling blood sugar require special efforts in the form of 5 pillars of sustainable DM so that BPJS utilization can be implemented as well as possible. It is also recommended for people with diabetes to better understand the flow of reference / use of BPJS as a basis for controlling blood sugar maximum.